2014
DOI: 10.21608/ejaj.2014.63689
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some Rhizobacteria as Induce Systemic Resistance or Bio-Control Agents in Controlling Root-knot Nematode, Meloidogyne incognita on Tomato

Abstract: Ten bacterial strains, selected from a bulk of isolates recovered from tomato rhizosphere, were tested for their ability to induce systemic resistance or bio-control agents against Meloidogyne incognita in tomato under greenhouse condition. Results showed that all ten tested bacterial strains showed significant reduction in nematode development and reproduction. The most effective strains were Methylomonas methanica, Bacillus cereus, Bacillus brevis and Obesumbacterium proteus. They were achieving the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…From the obtained results, it was noticed that one application of all the tested organic acids either as soil drenching induced tolerance to M. javanica in terms of the reduction in the tomato gall numbers and 2nd juveniles in the soil, these results are in partial agreement with (Anter et al, 2014 andAl-Ghonaimy andZawam, 2016) who found that soil drench of all inducers used on tomato roots reduced M. javanica reproduction.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…From the obtained results, it was noticed that one application of all the tested organic acids either as soil drenching induced tolerance to M. javanica in terms of the reduction in the tomato gall numbers and 2nd juveniles in the soil, these results are in partial agreement with (Anter et al, 2014 andAl-Ghonaimy andZawam, 2016) who found that soil drench of all inducers used on tomato roots reduced M. javanica reproduction.…”
Section: Discussionsupporting
confidence: 81%
“…There are a wide number of abiotic and biotic agents which can induce host resistance to the pathogen (Walters et al, 2013). Ascorbic acid, previously used for induction of plant resistance in plants (Abd-El-Kareem et al, 2013), can control different fungal diseases (Abdel-Kader et al, 2012 andShahda, 2000) and plant parasitic nematodes, such as root rot and Root-knot nematodes (Anter et al, 2014 andArrigoni et al, 1979). BABA is a non-protein amino acids that has been used as chemical inducers against a wide spectrum of pathogens in various plants (Oka et al, 1999;Lee et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These nematicidal compounds were originally isolated from Streptomyces avermitilis 30,31 , suggesting that environmental bacteria could be a good source of a myriad of bioactive metabolites. Previous studies have demonstrated that Actinobacteria and LAB have nematicidal activity 3032 . Thus, the goal of the present study was to isolate culturable putatively endophytic Actinobacteria and LAB from different tissues (needle, stem and root) of pine trees using MRS and HV media in search for possible biocontrol agents for PWN.…”
Section: Discussionmentioning
confidence: 99%
“…20 In the last few years, ISR mediated by plant growth-promoting bacteria (e.g. Bacillus sp., Klebsiella pneumoniae, Microbacterium maritypicum, R. etli) has been reported against a wide range of important plant-parasitic nematodes, such as H. glycines, 3,10,21 Meloidogyne incognita, 22 and Globodera pallida. 23 Moreover, GmACS9b, GmEDS1, GmPAD4, GmSAMT1, and GmNPR1-1 genes play an important role in induced systemic resistance against nematodes.…”
Section: Introductionmentioning
confidence: 99%